Alloplastic or Autologous? Bone Chips versus PEEK Cage for Lumbar Interbody Fusion in Degenerative Spondylolisthesis - Koehler, Stefan; Held, Christopher; Stetter, Christian; Westermaier, Thomas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Introduction This study was conducted to compare bone-filled intervertebral cages with autologous bone chips for instrumented lumbar interbody fusion in patients with spinal stenosis and degenerative spondylolisthesis.Methods Surgery consisted of posterior instrumentation and decompression, diskectomy, and intervertebral fusion using a polyetheretherketone (PEEK) cage surrounded and filled with spongious bone chips (group 1, n = 57) or spongious bone chips alone (group 2, n = 37). The choice of method was left to the discretion of the surgeon. Postoperative results were prospectively evaluated using a standardized protocol. Radiological assessment included fusion rates and vertebral height, while clinical assessment included the visual analog scale (VAS) and Oswestry Disability Index (ODI).Results In group 1, a mean of 1.38 ± 0.64 segments were fused. In group 2, a mean of 1.58 ± 0.65 segments were fused. In both groups, the VAS for back pain and leg pain and the ODI improved without significant differences between the two groups. Osseous fusion was documented by computerized tomography in 73% in group 1 and 89% in group 2 after a mean of 18 months. The loss of height was 2.8 ± 4.0% in group 1 and 2.4 ± 5.2% in group 2.Conclusion Regardless of whether a PEEK cage filled with spongious bone chips or spongious bone chips alone were used for lumbar interbody fusion, clinical parameters improved significantly after surgery. There were no significant differences in the rate of bony fusion and loss of height between the two groups. The results of this nonrandomized cohort study indicate that the implantation of autologous spongious bone chips harvested during the decompression procedure is a useful and cheap alternative to an intervertebral cage in patients with degenerative pseudospondylolisthesis.
Keywords: degenerative; spondylolisthesis; instrumented fusion; cage; PEEK; autologous; bone chips; spongious bone